Effects of Information Technology Application on Service Delivery by Cosmopolitan Savings and Credit Cooperative Organization, Nakuru County, Kenya - Lukania , Benson Joginda; Wafula , Raymond Ongus, (African Journal of Education,Science and Technology (AJEST), 2013)
Savings and Credit Cooperative Organizations (SACCOs) are seen as vehicles for resource mobilization as well as gateways to economic prosperity for families, especially those in lower and middle income categories. The main objective of the study was to analyze the effects of information technology application on service delivery by Cosmopolitan SACCO. Specifically, the study endeavoured to determine the influence of the use of automated teller machines (ATM) on service delivery by Cosmopolitan SACCO, to analyze the effect of telephone banking on service delivery by Cosmopolitan SACCO and to establish the extent to which branch networking has affected service delivery by Cosmopolitan SACCO. The research adopted a case study design in which 305 members of Cosmopolitan SACCO were randomly sampled from a total of 1286 members. Data was collected by administering questionnaires to the members of the SACCO at its banking hall. In addition, the SACCO’s managers were interviewed. The ensuing data was processed and analyzed by means of descriptive and inferential statistics, using the Statistical Package for Social Sciences (Version 17). The study established that information technology had contributed positively to improvement of service delivery by the SACCO. It also revealed that ATMs had the greatest influence on service delivery, followed by branch networking and telephone banking, respectively. It finally recommended, inter alia, that the SACCO should redouble its efforts of increasing awareness by members of available IT services, in order to maximize the usage of those services for carrying out routine transactions.